Screening of fungi of the genus Ganoderma and Trametes by the level of biomass synthesis under conditions of deep cultivation - Mustafin, K.G.; Bisko, N.A.; Kaliyeva А.К.; Narmuratova, Zh.B.; Zhakipbekova, A.S.; Sadueva, Zh.K. (Fundamental and Experimental Biology, 2022)
This article presents studies aimed at searching among the collection cultures of medicinal Ganoderma and Trametes fungal strains that are the most active in terms of growth rate and accumulation of biomass on nu-trient media of various compositions. 27 strains of the genus G. lucidum of different geographical origins and 29 strains of the genus Trametes (Fr.) from the collection of mushrooms of the N.G. Kholodny Institute of Botany of the National Academy of Sciences of Ukraine were studied. The radial growth rate of vegetative mycelium of the studied strains and their cultural and morphological features of growth on different nutrient media were examined. Certain differences were established between G. lucidum and T. versicolor fungal strains in terms of the level of biomass accumulation on media with different carbon and nitrogen sources. All the studied strains are able to grow at different carbon and nitrogen sources. The use of variance analysis of two-factor experience made it possible to detail the influence of nutrient sources, biological characteristics of strains, or their interaction on biomass biosynthesis. Based on the study of the cultural and morphological fea-tures of mycelial colonies, the radial growth rate of vegetative mycelium, the level of biomass accumulation on six types of liquid nutrient media it was found that the most productive strains in terms of biomass accumulation were T. versicolor 353 and G. lucidum 1621, which were selected for further research.